Production Analysis of Milkfish Culture in Kendal Regency, Central Java, Indonesia. - Harun, Hamroli (1992)
Low productivity is one of the serious problems in milkfish culture in Central Java, Indonesia. According to the Department of Fisheries Services of Central Java, the average annual production is about 526 kg per hectare. This average output is less than one third of that achievable in Taiwan. Therefore, it is expected that this yield can be increased. The question, then, is how to increase this yield. One way of approaching this problem is to examine factors that may affect the level of production in milkfish culture within the framework of a Cobb-Douglas production function. In this study, yield was specified as a function of six variable inputs (fry, labour, bestan pesticide, teodan pesticide, fert1l1zer and feed) and one fixed input (pond area). Individual variability of farmers such as their educational level, experience, participation in farmers organizations, and being visited by extension officials are also believed to affect milkfish yield. Therefore, these factors were also included in the regression model as independent variables. Aside from low productivity, a low level of income is also obvious among milkflsh farmers. The interesting question is how this low income could be increased in order to enable the farmers to survive. The way of approaching this problem was to examine the optimum rate of input use and to analyse the normalized restricted profit function, which we specified as a function of six normalized prices of variable inputs mentioned earlier. The results of this study indicate that all variable inputs hypothesized to explain yield variations in milkfish culture were significant except for pond area. It was also found that sociological factors hypothesized, except the number of Visits by extension officials, did influence yield significantly. The analysis on the optimum rate of inputs used also indicates that current input levels can be further raised in order to increase profitability.